Creating Metal Nanoparticle-Reduced Graphene Oxide Sheets by a Simple Desktop Method. Issue 1727 (8th October 2015) - Isseroff, Rebecca; Chen, Arthur; Blackburn, Lee; Lish, Justin; Kim, Jessica; Chen, Andrew; Kim, Tae Jin; Gentleman, Molly; Rafailovich, Miriam
ABSTRACT: We have previously reported on a simple desktop method for producing high quality reduced graphene oxide sheets (RGO) which involved dispersing graphene oxide in an ethanol-water solvent and reducing it with sodium borohydride. Metal salts can also be potent reducing agents. Here we show that when these salts are incorporated into the reduction process, metalized graphene sheets can be formed. Metallic salts were used to form Au, Pt, and AuPt nanoplatelets incorporated into the graphene structure. The nature of these metalized graphene platelets was then examined using FTIR, TEM, and SEM/EDAX. Raman spectroscopy of metalized graphene samples show peak shifts and increased D/G ratios over pure graphene, indicating an increased number of defects in the material and suggesting an attachment of metal atoms to the graphene surface. By using a minimum of metal while maximizing the surface contact area of the graphene sheet, these nanoparticle-RGO composites have potential for use in energy-producing devices and/or as catalysts.